Study on the growth mechanism of the internal oxide layer in 9% Ni cryogenic steel - Du, Hegang; Sun, Haoran; Cai, Minghui; Zuo, Xiurong (Frontiers in Materials, 2023)
The oxidation behavior of the Ni-rich layer in the internal oxide layer (IOL) in 9% Ni cryogenic steel is investigated at 1,150°C for 0–240 min in the air atmosphere. The morphology and phase composition of the Ni—rich layer are analyzed with energy dispersive spectroscopy, scanning electron microscopy, metallographic microscopy, and X—ray diffraction. The results show that the Ni—rich layer mainly consists of gray Fe3O4/FeO and white Ni–Fe particles, with a small amount of black Fe2SiO4. The morphologies of Ni–Fe particles undergo the following changes with isothermal oxidation time: dot—like → strip—like → net-like; at the same time, layered Ni–Fe particles were formed at about 1/3 of the thickness of the Ni—rich layer. Compared with the dot-like Ni–Fe particle, the net-like and layered Ni–Fe particles provide a fast path for the diffusion of O in the Ni—rich layer. However, the experimental steel still has a much lower oxidation rate because of the hindrance of Ni–Fe particles on the out-diffusion of Fe. During the oxidation process, the Kirkendall effect induces pores/cavities in the IOL, which weakens the stability of the IOL. In the end, the spalling phenomenon of the layered Ni–Fe particle occurs at 1,150°C for 180 min.